Compare the efficiency of colposcopic VIA, VILI, LIQUIPREP TM and conventional Pap smear; as screening procedure for carcinoma cervix - Subbaiyan, Nithya; Kasinathan, Sabari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Cancer of the cervix is a leading cause of morbidity and mortality among women worldwide. Therefore, to curb the disease, there is a need to develop a screening test that has good sensitivity and specificity. The aim is to compare the efficiency of Colposcopic Via, Vili, Liquiprep TM and conventional pap smear; as screening procedure for carcinoma cervix. Methods: This study was conducted in 100 women in the reproductive age. The pap smear and VIA are done in these cases. In positive cases, cervical biopsy and histopathological studies are done, the sensitivity and specificity of each test are determined and compared. Results: In this study, more cases belonged to 30 - 45 years age group. Among 100 women, 15% cases had high-grade lesion. Among high-grade lesions group, one case that is 6.7% had CIN 1, 73.3% had CIN2/3 and 3cases i.e., 20% had cervicitis. Among 100 women, 1% had ASCUS result, 10% belongs to HSIL group, 39% belongs to LSIL group and 2% had an unsatisfactory result. Conclusions: The lack of an effective and implementable screening programme lead to reporting of advanced cases of Ca Cervix. If detected at CIN or early Ca cervix stage, effective treatment can be provided with encouraging results. Therefore, effective and implementable Ca Cervix screening need to be provided in our country.